2018
DOI: 10.1002/ange.201801678
|View full text |Cite
|
Sign up to set email alerts
|

Regio‐ und chemoselektive Oxo‐Azidierung von Vinylarenen, katalysiert durch Kupfer(II) und sichtbares Licht

Abstract: Die photokatalytische Oxo-Azidierung von Vinylarenen mit Trimethylsilylazid und Luftsauerstoff als stçchiometrischem Oxidationsmittel gelingt in Gegenwart von [Cu(dap) 2 ]Cl oder [Cu(dap)Cl 2 ], im Unterschied zu etablierten Photokatalysytoren auf Basis von Iridium oder Ruthenium oder organischen Farbstoffen. Eine Erklärung hierfürsind der leichte Ligandenaustauschs owie die Mçglichkeit zur Rückbindung der intermediärg ebildeten Radikale an Kupferzentren. Als katalytischa ktive Spezies wird ein Cu II -Azid-Kom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 96 publications
(45 reference statements)
0
7
1
Order By: Relevance
“…[8] Additionally, Collins [30] and co-workers showed that the heteroleptic complex [Cu I (tmp)(BINAP)]BF 4 is an effective alternative in the photocatalytic Appel-type conversion of alcohols to the corresponding bromides developed by Stephenson [31] and co-workers in 2011. Gratifyingly, also [Cu II (dmp) 2 Cl]Cl was effective in this reaction yielding (1-bromoethyl)benzene (15) in synthetic useful yield of 73 % (Scheme 6), contrasting results previously reported for the homoleptic [Cu I (dmp) 2 ]Cl complex, which failed to achieve these transformations. [30] Scheme 6.…”
Section: Resultscontrasting
confidence: 56%
See 3 more Smart Citations
“…[8] Additionally, Collins [30] and co-workers showed that the heteroleptic complex [Cu I (tmp)(BINAP)]BF 4 is an effective alternative in the photocatalytic Appel-type conversion of alcohols to the corresponding bromides developed by Stephenson [31] and co-workers in 2011. Gratifyingly, also [Cu II (dmp) 2 Cl]Cl was effective in this reaction yielding (1-bromoethyl)benzene (15) in synthetic useful yield of 73 % (Scheme 6), contrasting results previously reported for the homoleptic [Cu I (dmp) 2 ]Cl complex, which failed to achieve these transformations. [30] Scheme 6.…”
Section: Resultscontrasting
confidence: 56%
“…Chlorosulfonylation, iodoperfluorination as well as CBr 4 -addition were performed on a 5.0 mmol scale giving rise to the desired photoproducts 3a, 8a and 10a in excellent yields (82-96 %) in gram quantities of 1.38-2.67 g highlighting the possible application of [Cu II (dmp) 2 Cl]Cl to produce synthetically useful quantities of product in ATRA reactions. So far, there are only few examples that consider ligand to metal charge transfer (LMCT) for Cu II complexes resulting in visible-light-induced homolysis (VLIH) to Cu I as a conceivable mechanistic proposal for photochemistry starting from Cu II complexes, [12,15,32] based on the pioneering study by Kochi investigating the photolysis of the Cu II -Cl-bond in CuCl 2 upon UV irradiation. [33] However, by now there is only scarce experimen-tal evidence present supporting this hypothesis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such photocatalysts have apparent advantages of strong absorption in the visible-light region, long-lived excited states, and high redox potentials of their excited states, but they also have several limitations in terms of rare earth reserves, high costs, and high toxicities . Hence, in the last several decades, continuous efforts have been devoted to explore alternative photocatalysts relied on more abundant, safe, and lower toxic metals such as copper. Nevertheless, in the early stage of development, only few reports were documented on copper-based photoactive complexes and their applications in visible-light-mediated organic transformations because of the lack of highly efficient copper-based photocatalysts (especially lack of those with long lifetime of excited states) . Later, with the introduction of N/N homoleptic and P/N heteroleptic Cu­(I)-photocatalysts, which are able to exhibit relatively long lifetimes of excited states, the field of copper-based visible-light photoredox catalysis indeed falls across the new phase of fast progress. ,, Despite some progress being made, the development of novel and efficient visible-light-driven radical reactions involving copper-based photosensitizers is still highly expected.…”
mentioning
confidence: 99%